2010
DOI: 10.1007/s11671-010-9611-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Contraction of Electrodeposited Bi/BiSb Superlattice Nanowires

Abstract: The lattice parameter of Bi/BiSb superlattice nanowire (SLNW) has been measured using in situ high-temperature X-ray diffraction method. The single crystalline Bi/BiSb SLNW arrays with different bilayer thicknesses have been fabricated within the porous anodic alumina membranes (AAMs) by a charge-controlled pulse electrodeposition. Different temperature dependences of the lattice parameter and thermal expansion coefficient were found for the SLNWs. It was found that the thermal expansion coefficient of the SLN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…12,13 Also, Bi/BiSb multilayer nanowires were synthesized by electrochemical deposition in AAO membranes. 14,15 The electrochemical deposition of Bi 1−x Sb x with controlled Sb concentration was reported by Besse et al for thin films. 16,17 Importantly, electrodeposition in etched ion-track templates enables to control the crystallinity of the nanowires by tuning the deposition conditions as well as their geometrical characteristics (diameter, shape, and surface morphology) given by the characteristics of the hosting channels.…”
Section: ■ Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…12,13 Also, Bi/BiSb multilayer nanowires were synthesized by electrochemical deposition in AAO membranes. 14,15 The electrochemical deposition of Bi 1−x Sb x with controlled Sb concentration was reported by Besse et al for thin films. 16,17 Importantly, electrodeposition in etched ion-track templates enables to control the crystallinity of the nanowires by tuning the deposition conditions as well as their geometrical characteristics (diameter, shape, and surface morphology) given by the characteristics of the hosting channels.…”
Section: ■ Introductionmentioning
confidence: 97%
“…Thus, by pressure injection in alumina (AAO) templates, Bi 1– x Sb x NWs with diameters 40 and 65 nm and x = 0.00, 0.05, 0.10, and 0.15 were fabricated . By electrochemical deposition, also in AAO templates, the growth of Bi 0.85 Sb 0.15 with diameter 40 and 200 nm was reported. , Using pulsed electrodeposition, Bi 1– x Sb x nanowires with a pronounced {110} texture for d = 50–80 nm and {110} and {202} for d = 22–60 nm have been obtained from an electrolyte based on hydrochloric acid in alumina. , Also, Bi/BiSb multilayer nanowires were synthesized by electrochemical deposition in AAO membranes. , The electrochemical deposition of Bi 1– x Sb x with controlled Sb concentration was reported by Besse et al for thin films. , Importantly, electrodeposition in etched ion-track templates enables to control the crystallinity of the nanowires by tuning the deposition conditions as well as their geometrical characteristics (diameter, shape, and surface morphology) given by the characteristics of the hosting channels. Recently, Hochbaum et al and Boukai et al reported an enhancement in ZT for Si NWs attributed to an increase in phonon scattering due to the roughness of the NW surface.…”
Section: Introductionmentioning
confidence: 99%
“…In a bulk material, the Weidmann-Franz law limits the ratio σ/ k , which makes optimization of ZT very difficult [ 5 , 6 ]. Recently, nanostructures lowering k and the distortion of electronic density of states enhancing S are effective approaches to enlarge ZT [ 7 - 10 ]. The ZT value of silicon nanowires is over 100-fold improvement up to ZT = 0.6 to 1 than that of bulk Si at near room temperature [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%